The Influence Of Blended Learning Face To Face Driver Model Type Learning On Learning Interests And Learning Outcomes In Simulation Digital - Hasna Amiratun Zafirah; Basori Basori; Dwi Maryono (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2021)
The purpose of this research is to find out how the influence of the use of blended learning model face to face driver model on student interest and learning outcomes. And to find out how effective the improvement in learning outcomes and learning interests of students uses blended learning type face to face driver model. The research method used in this study is an experimental method with true experimental design research design. The study involved class X TKJ students at SMK Sakti Gemolong as participants, who were selected using cluster random sampling techniques. The treatment given to the experimental class is in the form of a blended learning model face to face driver model, while the control class is done with conventional learning. The research method used is quantitative. Data were collected by questionnaire method and learning achievement test. Analysis of the questionnaire is used to obtain data on student interest in learning, then to the analysis of the learning outcomes test is used to obtain student learning outcomes data on the blended learning model face to face driver model. The results of this study are 1) there is an influence of the use of blended learning models face to face driver model on student learning outcomes with a significant level .836. 2) there is an influence of the use of blended learning type face to face driver model of learning interest of students with a significant level. 3) there is an effectiveness in increasing student learning outcomes by using blended learning models face to face driver model with a total score gain of 0.5142 compared to 0.4274 (control class). 4) there is effectiveness in increasing students' interest in learning by using a blended learning model face to face driver model with a total score gain of 0.2131 compared to 0.0740 (control class).